ADDITION OF POTENTIAL PROBIOTIC BACTERIA TO INCREASE GROWTH PERFORMANCE AND FEED EFFICIENCY OF COMMON CARP (Cyprinus carpio) - Yulvizar, Cut; Dewiyanti, Irma; Defira, Cut Nanda; Iqbalsyah, T.M.; Suhartono, Suhartono (Universitas Syiah Kuala, 2017)
Three intestinal bacteria isolates (namely C1, C2, and C3) from common carp (Cyprinus carpio) were isolated and identified as new potential probiotics. This research aimed to study the effect of three isolates potential probiotics addition on growth performance, survival rate and feed efficiency of common carp. Completely randomized design was assigned to fourth diet treatments with five replicates. As a control, we used the feed without any supplemention of potential probiotic. The result showed that the addition of potential probiotic bacteria (C1, C2, and C3) gave significant effect on daily growth rate, survival rate and feed efficiency and could be used in aquaculture industry to reduce feeding cost.